Two installations - Shirin Neshat, organized by Bill Horrigan. (Wexner Center for the Arts, The Ohio State University, 2000)
Photographs from black-and-white video/sound installations. The exhibition was presented between September 16 - December 31, 2000 in the Wexner Center for the Arts, Ohio State University.